2019
DOI: 10.1039/c9cc00268e
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of wire-in-plate nanostructured materials made of CoFe-LDH nanoplates coupled with Co(OH)2 nanowires grown on a Ni foam for a high-efficiency oxygen evolution reaction

Abstract: A series of wire-in-plate nanostructured electrocatalysts for OER with high catalytic activity were fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…electrocatalysts for their remarkable tunability of morphology, structure, and composition. [11] Various strategies, such as in situ growth by hydrothermal reaction, [12,13] electrodeposition, [14,15] layer-by-layer assembly, [16,17] and other combined multiple-steps processes, [18] were proposed to prepare various LDHs. Recently, many researchers have been attracted by an unusual synthesis method of etching precursor into hollow hierarchical structural LDHs.…”
mentioning
confidence: 99%
“…electrocatalysts for their remarkable tunability of morphology, structure, and composition. [11] Various strategies, such as in situ growth by hydrothermal reaction, [12,13] electrodeposition, [14,15] layer-by-layer assembly, [16,17] and other combined multiple-steps processes, [18] were proposed to prepare various LDHs. Recently, many researchers have been attracted by an unusual synthesis method of etching precursor into hollow hierarchical structural LDHs.…”
mentioning
confidence: 99%
“…Three relatively strong peaks at 44.51°(111), 51.85°(200) and 76.37°( 220) can be clearly distinguished and are attributed to metal nickel foam substrate (JCPDS 04-0850). [40] After obtaining LDH nanosheets through preliminary reactions, the main diffraction peaks appearing at 11.53°, 23.21°, 34.60°and 38.78°can be ascribed to (003), (006), (012) and (015) planes, respectively, which match well with the CoAl-LDHs phase (JCPDS 51-0045). [41] For the Ni 3 S 2 prepared separately, several well-defined peaks at 21.75°, 31.10°, 37.78°, 49.73°and 55.16°apart from the diffraction peaks of nickel foam can be corresponding to the respective (101), (110), (003), (113) and (122) crystal faces, confirming the existence of hexagonal Ni 3 S 2 (JCPDS 44-1418).…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies have suggested that N-doping can activate nearby carbon atoms, and thus increase the active sites [ 27 , 28 ]. For the C1s spectrum ( Figure 2 c), the main peak at 284.8 eV is related to the C=C bonds [ 29 , 30 ], and the other two peaks at higher binding energies of 286.5 and 289.3 eV are ascribed to the oxygen-containing groups of C–O and O–C=O, respectively [ 31 , 32 ]. Additionally, the peak located at 285.4 eV is ascribed to C=N [ 33 , 34 ], suggesting the successful nitrogen-doping of PC via the soft nitriding processing [ 35 ].The high-resolution Pd 3d core level spectrum ( Figure 2 d) can be divided into two groups peaks corresponding to oxidized Pd species as a result of the oxidation occurred on the surface of the catalyst during the preparation and characterization procedures.…”
Section: Resultsmentioning
confidence: 99%